DESENVOLVIMENTO DE UM SISTEMA DE SENSORIAMENTO ÓPTICO APLICADO À BIOENGENHARIA TECIDUAL DE ÓRGÃOS DESCELULARIZADOS - Pereira, Rayssa Helena Arruda (2020)
The subjectivity of the final evaluation of the decellularized individual organs is one of the main problems of the decellularization technique, which can restrict the reproducibility of the cellular repopulation and the transplants responses. Thus, our s